PERAN GURU DALAM MENUMBUHKAN RASA NASIONALISME SISWA KELAS V SDN 5 NAGRI KALER - Mustikaati, Wina; Muharam, Agus; Khoirunnisa, Anis; Khusnah, Kharisma Nurul; Rakasiwi, Neng Putri (JURNAL SINEKTIK, 2023)
Educators have an important role in the continuity of the teaching and learning process. Law No. 14 of 2005 concerning Teachers and Lecturers Article 4 states that teachers play a role as actors in the learning process and have a function in improving the quality of national education for the better. The purpose of the observations made is to obtain effective roles and methods to foster a sense of nationalism in students. Qualitative research is a type of method used when research takes place. The research was conducted through observation, interview results and documentary evidence in obtaining actual data from the field. The teacher's role in instilling a sense of nationalism in students is manifested in the classroom through Internship subjects which are closely related to everyday life in the teaching and learning process. The research discusses how to instill a sense of nationalism in elementary school children through PKN learning in class, flag ceremonies and scout activities. The existence of this research is beneficial for the people of Indonesia, especially in elementary schools, because it can instill a sense of nationalism through PKN learning